A Late Iron IIA Destruction Layer at Tel Aphek in the Sharon Plain. (October 2015) - Kleiman, Assaf
Abstract : The article deals with a late Iron IIA destruction layer at Tel Aphek in the Sharon Plain. The remains, which were uncovered during Moshe Kochavi and Pirhiya Beck's excavations, have important implications for the history of the central Coastal Plain. The study of the finds suggests that during the late Iron IIA, Aphek increased in size, and that the ceramic tradition of the town exhibited similarities to that of the Northern Kingdom. This may be explained against the background of Israelite expansion to the coast during the 9th century BCE. Detailed analysis of the pottery repertoire indicates that Aphek was destroyed during the final phase of the Iron IIA, presumably in the course of an Aramean military campaign to the south.